Systems, software and services process improvement : 25th European Conference, EuroSPI 2018, Bilbao, Spain, September 5-7, 2018, Proceedings /: 25th European Conference, EuroSPI 2018, Bilbao, Spain, September 5-7, 2018, Proceedings. (2018) - Unknown
No abstract available